Exploring Student Awareness of Sentence Construction: The Role of Misplaced Words and Phrases in One-Clause Sentences - Julaika, Siti; Hasanah, Nur; Aswatdi, Hazhar; Sari, Khoiriya; Gani, Liyundzira Fikroh; Ismahani, Siti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research explores students' awareness of sentence construction, focusing on the role of misplaced words and phrases in one-clause sentences. This issue poses a significant challenge for English as a Foreign Language (EFL) learners, especially in Indonesia, where these errors often obscure meaning and hinder effective communication. This study uses a descriptive qualitative approach to understand how students realize common sentence construction errors, such as dangling and ambiguous modifiers. Through semi-structured interviews and classroom observations, it was found that mother tongue interference and inadequate teaching methods contribute to students' difficulties in accurate sentence construction. The findings suggest the need for a more focused teaching approach to improve students' understanding of correct sentence structure and to help them identify and correct errors independently.